2003
DOI: 10.1038/sj.ejhg.5201048
|View full text |Cite
|
Sign up to set email alerts
|

Parametric and nonparametric genome scan analyses for human handedness

Abstract: We have performed a genome scan using 25 nuclear families consisting of right-handed parents with at least two left-handed children. Handedness was assessed as a qualitative trait using a laterality quotient. Laterality quotients indicate the direction of handedness, which is hand preference for performing unimanual tasks. Both parametric and nonparametric linkage analyses were applied. The parametric analysis using the single-locus genetic model of Klar resulted in four different regions with LOD scores highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…To our knowledge, a relationship between these chromosomal regions and side preference has not been reported previously. We did not find evidence for linkage in candidate regions identified by Francks et al on chromosomes 2p12Áq11 (Francks et al, 2002;Francks et al, 2003a), 10ptel (Francks et al, 2003c), and 17p11 Áq23 (Francks et al, 2002), and by Van Agtmael et al (2003) on chromosome 10q26. This lack of concordance is perhaps not surprising given the general difficulty of replicating linkage signals for complex traits.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, a relationship between these chromosomal regions and side preference has not been reported previously. We did not find evidence for linkage in candidate regions identified by Francks et al on chromosomes 2p12Áq11 (Francks et al, 2002;Francks et al, 2003a), 10ptel (Francks et al, 2003c), and 17p11 Áq23 (Francks et al, 2002), and by Van Agtmael et al (2003) on chromosome 10q26. This lack of concordance is perhaps not surprising given the general difficulty of replicating linkage signals for complex traits.…”
Section: Discussioncontrasting
confidence: 91%
“…Although segregation analysis in the extended pedigree produced suggestive results for the NODAL and DNAHC13 regions of chromosomes 10 and 14 respectively, linkage analyses conducted on the nuclear and extended families failed to support a role for the candidate regions in handedness as modelled by Klar (1996) or McManus (1985). However, in a later study of Australian nuclear families, Van Agtmael et al (2003) found suggestive evidence of genetic linkage for handedness on chromosome 10q26, and additional LODs with values between 1 and 2 on chromosomes 10p12.33, 12q24.3, and 14q22. In separate studies of reading-disabled sibling pairs from the UK, Francks et al identified putative quantitative trait loci (QTLs) for hand motor skill on chromosome 10ptel (Francks et al, 2003c), and for relative hand skill on chromosome 2p12 Áq11 (Francks et al, 2002).…”
Section: Duggirala C Thomas D Dyer C and Laura Almasymentioning
confidence: 89%
See 1 more Smart Citation
“…The QTL located at 2p12-q11 was further confirmed in a study of left-handed brothers (Francks et al 2003a) and showed a parent-of-origin effect ( Francks et al 2003b). In a study of 25 Australian nuclear families, Van Agtmael et al (2003) found genetic linkage for handedness on chromosome region 10q26 using a laterality quotient computed from questionnaires. In 584 Mexican-Americans, Warren et al (2006) identified a linkage signal for drawing and writing handedness, assessed by questionnaire, within chromosome region 12q21-23.…”
Section: Genetic Factors (A) Handedness In Familiesmentioning
confidence: 76%
“…Van Agtmael et al (2001) found no evidence for linkage to chromosome 7 but possible linkage to chromosome 10 (Van Agtmael et al, 2002;Van Agtmael et al, 2003). Medland et al (2006) found a genetic influence on handedness in twins, along with considerable individual variability.…”
Section: Non-genetic Influences On Human Lateralizationmentioning
confidence: 99%